Frequency of postmortem ethanol formation in blood, urine and vitreous humor – Improving diagnostic accuracy with the use of ethylsulphate and putrefactive alcohols. (February 2022) - Oshaug, Katja; Kronstrand, Robert; Kugelberg, Fredrik C.; Kristoffersen, Lena; Mørland, Jørg; Høiseth, Gudrun
Highlights: In 24% of ethanol positive autopsy cases, some postmortem formation occurred. In 15% of blood ethanol positive autopsy cases, all ethanol was formed postmortem. Postmortem formed ethanol was also present in urine and vitreous humor. Urine and vitreous humor to blood ratios were lower when ethanol was formed. Graphical Abstract: ga1 Abstract: Purpose: This study aimed to compare the frequency of postmortem ethanol formation in blood, urine and vitreous humor according to negative ethylsulphate (EtS) in blood or positive putrefactive alcohols (PA's) in either medium. Furthermore, it aimed to evaluate the interpretational value of calculated ethanol ratios in relation to EtS and PA results. Methods: Blood ethanol positive forensic cases were included; one dataset consisting of 2504 cases with EtS analysed in blood and another dataset with 8001 cases where PA's were analysed. Results: PA's were found in 24.4% of cases. EtS was negative in 15.3%, 9.4% and 7.4% of cases that were positive for ethanol in blood, urine and vitreous humor, respectively. In EtS negative cases, the concentrations of ethanol in blood, urine and vitreous humor were lower than 0.20 g/kg in 51.3%, 67.4% and 77.8%, respectively. It was 1.0 g/kg or higher in blood in 4.2% of cases. More EtS negative and PA positive cases were seen in central compared to peripheral blood. Ethanol ratios between urine or vitreous humor and blood were significantly lower in both EtS negative and PA positive cases, but large variations were observed. Conclusion: EtS and PA analysis improve the diagnostic accuracy of ethanol in postmortem cases. Postmortem ethanol formation in vitreous humor and urine were both more frequent than expected and we recommend the analysis of ethanol primarily in peripheral blood if available.